1976
DOI: 10.1128/aem.31.1.29-34.1976
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of phthalic acid esters in river water and activated sludge

Abstract: The primary and ultimate biodegradability ofphthalic acid, monobutyl phthalate, and five structurally diverse phthalic acid ester plasticizers in river water and activated sludge samples were determined via ultraviolet spectrophotometry, gas chromatography, and CO2 evolution. The compounds studied underwent rapid primary biodegradation in both unacclimated river water and acclimated activated sludge. When activated sludge acclimated to phthalic acid esters was used as the inoculum for the CO2 evolution procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(33 citation statements)
references
References 16 publications
(11 reference statements)
1
31
0
1
Order By: Relevance
“…This release has raised considerable concerns, as recent studies have suggested that common plasticizers may not be entirely benign and completely biodegradable, as originally thought [3,4]. Plasticizers and their metabolites have been found in environmental samples of soil [5][6][7][8], surface water [9][10][11][12], and the tissue of mammals [13][14][15]. Plasticizers have also been found to bioconcentrate and bioaccumulate in some species of fish and amphibians, where they were found to be carcinogenic and to interfere with reproduction [13].…”
Section: Introductionmentioning
confidence: 99%
“…This release has raised considerable concerns, as recent studies have suggested that common plasticizers may not be entirely benign and completely biodegradable, as originally thought [3,4]. Plasticizers and their metabolites have been found in environmental samples of soil [5][6][7][8], surface water [9][10][11][12], and the tissue of mammals [13][14][15]. Plasticizers have also been found to bioconcentrate and bioaccumulate in some species of fish and amphibians, where they were found to be carcinogenic and to interfere with reproduction [13].…”
Section: Introductionmentioning
confidence: 99%
“…Longer halflives may occur in anaerobic, oligotrophic, or cold environments. Biodegradation is considered to be the most significant aquatic fate process for phthalate esters [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be released from the material while being used 2. Plasticizers and their metabolites have been found in environmental samples of soil3–6 and surface water 7–10. The most widespread material in the production of blood storage bags, haemodialysis and drain tubes or catheters is PVC plasticized with di(2‐ethylhexyl)phthalate (DEHP).…”
Section: Introductionmentioning
confidence: 99%